Resonant Magnetoelectric Coupling of Fe-Si-B/Pb(Zr,Ti)O3 Laminated Composites with Surface Crystalline Layers - Yu Sun; Xu Zhang; Sheng Wu; Nian Jiang; Xin Zhuang; Bin Yan; Feng Zhang; Christophe Dolabdjian; Guangyou Fang (Sensors, 2023)
The resonant magnetoelectric (ME) effect of Fe78Si9B13/Pb(Zr,Ti)O3 (FeSiB/PZT) composites with a surface-modified Fe78Si9B13 amorphous alloy has been studied. The surface-modified FeSiB can improve the ME coefficient at the resonant frequency by optimizing the magnetomechancial power conversion efficiency. The maximum ME coefficient of the surface-modified ribbons combined with soft PZT (PZT5) is two-thirds larger than that of the composites with fully amorphous ribbons. Meanwhile, the maximum value of the ME coefficient with surface-modified FeSiB ribbons and hard PZT (PZT8) is one-third higher compared with the fully amorphous composites. In addition, experimental results of magnetomechanical coupling properties of FeSiB/PZT composites with or without piezoelectric layers indicate that the power efficiency of the composites first decreases and then increases with the increase in the number of FeSiB layers. When the surface crystalline FeSiB ribbons are combined with a commercially available hard piezoelectric ceramic plate, the maximum magnetoelectric coupling coefficient of the ME composite reaches 5522 V/(Oe*cm), of which the electromechanical resonant frequency is 23.89 kHz.